2016
DOI: 10.1007/s11302-016-9531-6
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine arrests breast cancer cell motility by A3 receptor stimulation

Abstract: In neutrophils, adenosine triphosphate (ATP) release and autocrine purinergic signaling regulate coordinated cell motility during chemotaxis. Here, we studied whether similar mechanisms regulate the motility of breast cancer cells. While neutrophils and benign human mammary epithelial cells (HMEC) form a single leading edge, MDA-MB-231 breast cancer cells possess multiple leading edges enriched with A3 adenosine receptors. Compared to HMEC, MDA-MB-231 cells overexpress the ectonucleotidases ENPP1 and CD73, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
(91 reference statements)
0
20
0
Order By: Relevance
“…Specifically, A 3 AR is translocated to the neutrophil leading edge, and adenosine generated by ecto-ATPases/nucleotidases results in autocrine stimulation of A 3 AR-enhanced polarized migration, following its initiation by ATP activating the P2Y 2 receptor. 34,[261][262][263] This was confirmed also in a sepsis model of A 3 AR knockout (KO) mice where a reduction in the recruitment of neutrophils to the lung and peritoneum was observed. 264 In contrast, in human breast cancer cells, the A 3 AR is expressed in multiple leading edges where it promotes cell migration with numerous directional changes.…”
Section: Preclinical Studies In Immune Cellsmentioning
confidence: 67%
See 2 more Smart Citations
“…Specifically, A 3 AR is translocated to the neutrophil leading edge, and adenosine generated by ecto-ATPases/nucleotidases results in autocrine stimulation of A 3 AR-enhanced polarized migration, following its initiation by ATP activating the P2Y 2 receptor. 34,[261][262][263] This was confirmed also in a sepsis model of A 3 AR knockout (KO) mice where a reduction in the recruitment of neutrophils to the lung and peritoneum was observed. 264 In contrast, in human breast cancer cells, the A 3 AR is expressed in multiple leading edges where it promotes cell migration with numerous directional changes.…”
Section: Preclinical Studies In Immune Cellsmentioning
confidence: 67%
“…In recent years, it has been reported that the A 3 AR is distributed in a highly polarized fashion on the neutrophils cell membrane and contribute to their chemotaxis and migration. Specifically, A 3 AR is translocated to the neutrophil leading edge, and adenosine generated by ecto‐ATPases/nucleotidases results in autocrine stimulation of A 3 AR‐enhanced polarized migration, following its initiation by ATP activating the P2Y 2 receptor . This was confirmed also in a sepsis model of A 3 AR knockout (KO) mice where a reduction in the recruitment of neutrophils to the lung and peritoneum was observed .…”
Section: Biological Role and Therapeutic Applications In Models Of Immentioning
confidence: 76%
See 1 more Smart Citation
“…The adenosine machinery also mediates its effects directly in tumour cells by affecting their proliferation and cell death through recruitment of different receptors. In particular, opposite effects on cell growth and motility have been observed, with A 1 , A 2A and A 2B receptors being promoters whilst A 3 receptors are inhibitors of cell proliferation (Merighi et al , ; ; Gessi et al , ; Antonioli et al , ; Borea et al , ; Ledderose et al , ). Indeed, it is important to note that clinical trials are undergoing for A 3 receptor agonists, based on their antiproliferative effects, representing an opportunity for new anticancer drugs (Borea et al , ).…”
Section: Pathological Role Of Adenosine In Cancermentioning
confidence: 99%
“…Dominant positive expression of URE3-BP in Eh induced an elongated morphology which was reported to be highly invasive (Gilchrist et al, 2010), and so the polarized form may have an important role in the pathogenesis. The role of adenosine receptors on cell motility indicted the possibility of purinergic signaling (Chen et al, 2006;Ledderose et al, 2016) in controlling motility and chemotaxis of Entamoeba. Animal cells contain 5-10 mM of ATP in their cytosol, and the tissue damage by Entamoeba may cause leakage of ATP from damaged cells.…”
Section: Pentoxifylline Effects Are Mediated By Adenosine Receptorsmentioning
confidence: 99%